Teachers who Initiate Changes with an Ebook-Integrated Curriculum: Revisiting the Developmental Assumptions of Stages of Concerns in the Concerns-Based Adoption Model - Min, Mina (Alberta Journal of Educational Research, 2017)
Understanding teachers’ concerns about integrating new technology to their curricular practices is essential for the improvement of pedagogical practices. Using in-depth interviews, this study aims 1) to explore and describe concerns of teachers who attempted to initiate ebook-integrated curriculum independently in a higher education setting, and 2) to examine how well the Stages of Concerns (SoC) in Concerns-Based Adoption Model (CBAM) explains the change processes of the teachers. This study challenges the developmental assumptions underlying the SoC in CBAM and suggests that the theoretical framework must address individuals’ idiosyncratic traits as a contextual factor to better explain the change processes of teachers who initiate change in higher education. Additionally, future research directions pertaining to the adoption of innovations by teachers are suggested. Afin d’améliorer les pratiques pédagogiques, il est essentiel de comprendre les préoccupations qu’ont les enseignants par rapport à l’intégration de la nouvelle technologie à leurs pratiques pédagogiques. Reposant sur des entrevues en profondeur, cette étude a comme objectif, d’une part, d’explorer et de décrire les préoccupations d’enseignants qui ont tenté, de façon autonome, d’initier un programme d’études intégrant des livres électroniques dans un milieu universitaire, et d’autre part, d’examiner la mesure dans laquelle les étapes de préoccupation du modèle d’adoption reposant sur les préoccupations (Concerns-Based Adoption Model – CBAM) réussissent à expliquer les processus de changement chez les enseignants. Cette étude remet en question les hypothèses développementales sur lesquelles sont fondées les étapes de préoccupation du CBAM et propose que le cadre théorique doit considérer l’idiosyncrasie des gens comme facteur contextuel pour mieux comprendre les processus de changement des enseignants qui initient des changements dans les milieux universitaires. Nous proposons également des orientations de recherche à l’avenir portant sur l’adoption d’innovations par les enseignants.